Frequency of Laboratory Monitoring of Chronic Medications Administered to Nursing Facility Residents: Results of a National Internet-Based Study - Handler, Steven M. (2008)
OBJECTIVE: To determine the minimal frequency of laboratory monitoring of 30 types of chronic medications or classes that are administered to nursing facility residents and are either listed under pharmacy services tag F329 (the tag for unnecessary medications), or have a narrow therapeutic index. DESIGN AND SETTING: Cross-sectional, Internet-based survey. PARTICIPANTS: National sample of 500 pharmacists, 500 nurse practitioners, and 327 physicians. MAIN OUTCOME MEASURE: Minimal frequency of monitoring, recorded as an interval of 1, 3, 6, 9, or 12 months, for each of 35 laboratory parameters (e.g., serum drug level, complete blood count, liver function tests) for the 30 types of chronic medications or classes. Agreement was defined as having two or more of the three professional groups select the same minimal monitoring interval. RESULTS: Overall, 116 professionals (20 pharmacists, 48 physicians, and 48 nurse practitioners) completed the survey. Most respondents were women (58.6% [68/116]), and most had worked in nursing facilities for > 5 years (66.4% [77/116]). Regarding minimal laboratory monitoring intervals, respondents reached agreement concerning 33 of 35 parameters. They selected three or six months as the minimum interval for 30 of 35 parameters (85.7%), one month as the minimum for two parameters, and 12 months as the minimum for one parameter. CONCLUSION: The multidisciplinary panel agreed that most medications that were listed under the F329 tag or have a narrow therapeutic index should have laboratory monitoring every three or six months. The results can be used by nursing facility professionals to establish minimal laboratory monitoring parameters for chronic medications, which may potentially reduce the occurrence of adverse drug reactions.